Virtual residency recruitment: future directions in the new era. (31st December 2022) - Breitkopf, Daniel; Albold, Cheryll; Barlow, Jonathan; Bellamkonda, Venkatesh; Dorcent, Claire; Sadosty, Annie; Clarke, Michelle; Cabrera, Daniel
Abstract: Introduction: The COVID-19 pandemic led to many changes in healthcare including graduate medical education (GME). Residency and fellowship programs halted in-person recruitment and pivoted to virtual models. Residency selection and recruitment were practices ripe for redesign, as they relied on in-person interviewing as the major point of contact prior to match list creation. In this commentary, we review the state of virtual interviewing and propose a future state where virtual interactions are commonplace and integrated into a comprehensive recruitment process. Discussion: Virtual recruitment has led to a reduction of expenses, improved time efficiency for all parties and a reduced carbon footprint. Residency match outcomes have not changed substantially with the advent of virtual interviewing. Hybrid approaches, including virtual and in-person options have significant drawbacks and pitfalls which may limit adoption. Given the upheaval in GME recruitment caused by the pandemic, and the limitations of current methods for candidate assessment and interactions with programs, further innovation is needed to achieve an optimal state for all stakeholders. Multiple technology innovations are on the horizon which may improve the ability to interact virtually. Adoption of new technology along with expanding the timeline for residency recruitment may further optimize the process for both applicants and programs. Conclusions: The GME community was able to adopt technology for the recruitment interview rapidly due to the pandemic. As more opportunities for technology-based interactions grow, the opportunity exists to reimagine recruitment beyond the interview. While resources are constrained, some of the efficiencies gained by adopting virtual interviewing can be leveraged to expand the interactions between programs and applicants. Incorporation of in-person interaction may still be needed. Models will need to be developed to build upon the best characteristics of the virtual and in-person environments to optimize GME recruitment. KEY MESSAGES: Virtual communication methods have substantially changed residency recruitment during the COVID -19 pandemic. COVID -19 related changes in residency recruitment, including wide adoption of virtual methods, should be maintained and strengthened. Efforts should be made to advance the gains in residency recruitment strategy during the pandemic by use of technologies that expand virtual interactions beyond the interview.